1933 N.Y. Laws 1638–39, ch. 805, §§ 1, 3 - (:unkn) unknown (General Publisher, 1933)
Prohibited selling, giving, disposing of, transporting, or possessing a machine gun or submachine gun to a person guilty of a felony.
--
Keywords: MACHINE GUN RESTRICTION